What if we focus on developing commonalities? Results of an international and interdisciplinary Delphi study on transcultural competence - Baumann Montecinos, Julika; Grünfelder, Tobias (International journal of intercultural relations, 2022)
This article seeks to articulate an invitation to rethink the success factors of global cooperation by using a relational approach. It presents the initial results of a 3-stage Delphi study that was conducted in 2020 with a panel of around 50 experts from different countries and disciplines in order to better understand the concept of transcultural competence. The study questions specifically invited the experts to focus on (1) the determinants of people’s perceptions of cultural diversity, (2) the role and creation of commonalities, (3) the competences that support an approach to cultural diversity aiming at commonalities, and (4) the formulation of corresponding conceptual conclusions as a point of departure for further research and practical application. The results suggest that a relational view could be interpreted as a common denominator within the Delphi group. Following such a relational approach, the core aspirations of a revisited concept of transculturality include to consider individuums in their relations, to refer to context-specific events, constructive processes and the connotation of the beyond, which implies the possibility, ability and willingness of creating new commonalities (without excluding the existence of differences). A relational understanding of cultural complexity thus views cultural commonalities and differences not as opposites, but as complementary resources for cooperation. It thereby hints towards a process-perspective of competence, as well as towards the departure from a static concept of identity in favor of the concept of belonging, which is inherently relational. •Delphi study maps the current discussions in the field of inter- and cross-cultural studies and subjects them to a moderated process of reflection.•The results suggest that a relational perspective on cultural complexity is a common denominator within the Delphi group.•Such a perspective considers individuals in their relations and takes the relation as its unit of analysis.•Cultural commonalities and differences are not opposites, but complementary resources for cooperation.•A relational concept of transculturality refers to context-specific events, constructive processes, and the connotation of the beyond.•The "beyond" implies the possibility, ability and willingness of creating new commonalities in cultural complexity.